2018
DOI: 10.1017/ice.2018.37
|View full text |Cite
|
Sign up to set email alerts
|

Time to Detection in Culture Supports Prediction of Low Transmissibility of Tuberculosis and Discontinuation of Isolation for Low-Risk Patients With A Single AFB-Negative and NAAT-Negative Respiratory Specimen

Abstract: For 94 patients with culture-positive pulmonary tuberculosis, time-to-detection (TTD), acid-fast bacilli (AFB) smear, and nucleic acid amplification test (NAAT) results were reviewed. All 12 patients whose first specimen was negative by AFB smear and NAAT had prolonged TTD, indicating low transmissibility and supporting discontinuing isolation for low-risk patients.Infect Control Hosp Epidemiol 2018;39:619-621.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…In this study, TDG exceeded the 4-5 week duration reported by several authors as sufficient for identifying all culture positive samples (Pfyffer and Wittwer, 2012;Tyrrell et al, 2012;Ogwang et al, 2015;Khan et al, 2018). Indeed, 90 th centile for TDG of all samples was 55 days, and even 58 days in smear negative cases.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…In this study, TDG exceeded the 4-5 week duration reported by several authors as sufficient for identifying all culture positive samples (Pfyffer and Wittwer, 2012;Tyrrell et al, 2012;Ogwang et al, 2015;Khan et al, 2018). Indeed, 90 th centile for TDG of all samples was 55 days, and even 58 days in smear negative cases.…”
Section: Discussioncontrasting
confidence: 63%
“…The rationale of this selection of samples was as follows: 1/large scale implementation of Xpert/MTB-RIF has increased same-day diagnosis, with a diagnostic sensitivity exceeding 80% in culture positive samples, irrespective of microscopy ( Boehme et al, 2011 ; Khan et al, 2018 ); 2/in patients who do not have a same-day diagnosis by Xpert/MTB-RIF (negative test or not performed because of sample size), and who will eventually become culture positive, TDG determines when a diagnosis MTB can either be confirmed (as well as drug sensitivity profile), or reasonably excluded (treatment will most often have been started based on clinical suspicion). Our focus was therefore on TDG for all culture positive clinical samples fulfilling these criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations